Philippine monascus red rice wine - Paglinawan, Jennibeth Fornis
ABSTRACT The study was undertaken to develop Philippine Monascus red rice wine by adapting a 2-level fermentation process, a local Monascus sp. isolate (UPCC 3765) and a native fermentation starter for producing tapuy called bubod. The G25N agar was found to be effective in propagating Monascus sp. UPCC 3765 in terms of color and maturity after 7-14 d incubation at 37 ºC. The adaptation of the 2-level fermentation process was found to be an effective way of increasing the alcohol content of Monascus red rice wine to 18-20% as compared to the relatively low alcohol content of the local rice wine tapuy. The sensory properties of the Philippine Monascus red rice wine produced that was aged for 2 months was found to be more acceptable than the 1 week old test rice wines. The rice wine produced had a golden yellow to orange color, fragrant with light rice-like aroma and moderate alcohol aroma, smooth mouthfeel, soft acidity and rich rice-wine flavor that were immediately perceived across the palate upon tasting but does not linger on the mouth. The test rice wine was not intensely dry with an aftertaste that was not too bitter. It was recommended to have further studies on the improvement of sensory attributes of the Monascus red rice wine through low temperature and longer 2-level fermentation process. Another recommendation was to study the water and alcohol solubilities of the Monascus pigments from the rice wine for other possible food applications.